Altering ROY polymorph crystallization in conventional and microfluidic crystallizers with acoustic cavitation - Mohammed Noorul Hussain; Arthur Demuynck; Tom Van Gerven (Scientific Reports)
Abstract Selective crystallization of polymorphs can be a difficult task, influenced by several physical and chemical parameters like mixing, temperature, supersaturation, solvent, etc. Acoustic cavitation, produced at low ultrasonic frequencies, induces effects like micro-mixing and local heating which, when coupled to crystallization, can alter crystal form nucleation. In this work, anti-solvent crystallization of a model compound (ROY) was conducted to investigate the effect of acoustic cavitation on polymorph nucleation. Experiments were conducted in batch and microfluidic flow crystallization setups at different anti-solvent volume fractions under silent and sonicated conditions. Results show that sonication has a significant effect on the polymorphic outcome. In batch crystallization sonication promoted the formation of the stable Y form. This observation was consistent for flow crystallization experiments at a low flow rate. At a higher flow rate, this effect weakened due to low residence times. In some batch experiments recorded with a high speed camera it was found that the formation of the Y form was most probably facilitated by ultrasound enhanced polymorphic transformation rather than direct nucleation. Additionally, computational fluid dynamic simulations (only silent-flow conditions) indicate that supersaturation distribution within the channel has a significant effect on the polymorph nucleated.